WhatsApp Application in Texts Agricultural for Students of Universitas Negeri Makassar: analysis litotes - Azis Azis; Juanda Juanda; Asri Ismail (Universitas Negeri Makassar, 2022)
Abstract. Abstract. This research has an impact on the field of language, especially scientific development in the structure of the figure of speech as part of semantics. The research problem is how is the basis of the structure of agricultural text-based litotes for students at the Faculty of Languages and Literature, Universitas Negeri Makassar. This research is different from the others because its main point is the base of the litotes structure with an emphasis on agricultural texts with whatsapp application. The content analysis method is used to reveal the data. The research sample was 120 students with data in the form of words and phrases in agricultural texts. The findings are that the root of the litotes structure in the form of nouns (11%), numerals (5%), adverbs (47%), adjectives (37%) have an unstable position in the text. Including noun phrases (20%), numerals phrases (10%), adjective phrases (70%) sometimes appear sequentially and especially the structure of adjective phrases occupies the smallest scope; the role as action (40%), experience (40%), luck (20%) in the text there is an imbalance.